MANAJEMEN PEMBELAJARAN GURU PADA SD NEGERI 1 PEUKAN PIDIE KABUPATEN PIDIE - Nora Feri, Cut Zahri Harun, Nasir Usman (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
Abstract: Learning management includes several matters, such as planning, implementation, and supporting and inhibiting factors of learning. This study aimed at determining the learning plan, the learning implementation, learning evaluation, and supporting and inhibiting factors in teacher learning management. The research method used was descriptive with a qualitative approach. The data were collected by observation, interviews and documentation review. The subjects of the study were principals and teachers. Data were analyzed with reduction, display, and verification techniques. The results showed that: 1) planning of learning made by teachers had not planned properly, there were some teachers who had not been able to prepare mapping properly, preparation of topic, and syllabus as tool that should be prepared before preparing the lesson plan; 2) the implementation of teacher learning done by teachers was guided by school-based curriculum. The implementation of the learning process was not optimal, for it was still a lack of teacher knowledge about the procedure of effective learning application, and there was still a low-grade teacher who used the subjects clearly without topic; 3) the evaluation of learning done by teachers was guided by a lesson plan. The evaluation was done to improve the learning activities of teachers, both spoken and written evaluation forms; and 4) the obstacles to the implementation of learning management were planning for coaching teachers, time, facilities and personnel. In addition, it lacks training for teachers; some teachers were not active in group activities, seminars, and improving the teaching professional.Keywords: Teacher, Learning Management, and SD Negeri 1 Peukan Pidie.Abstrak: Penelitian ini bertujuan untuk mengetahui perencanaan pembelajaran, pelaksanaan pembelajaran, evaluasi pembelajaran, serta faktor-faktor pendukung dan penghambat dalam manajemen pembelajaran guru. Metode penelitian ini bersifat deskriptif analitis dengan pendekatan kualitatif. Pengumpulan data menggunakan teknik observasi, wawancara, dan dokumensi. Subjek penelitian adalah kepala sekolah dan guru. Hasil penelitian menunjukkan bahwa: 1) Perencanaan pembelajaran guru belum diprogramkan dengan baik, ada guru yang belum mampu menyusun pemetaaan dengan baik, penyusunan jaringan tema, dan penyusunan silabus sebagai perangkat yang harus dipersiapkan sebelum menyusun RPP; 2) Pelaksanaan pembelajaran guru yang dilaksanakan berpedoman pada Kurikulum Tingkat Satuan Pelajaran. Pelaksanaannya belum optimal, masih kurangnya pengetahuan guru tentang tata cata penerapan pembelajaran tersebut secara efektif, serta masih ada guru kelas rendah yang menggunakan mata pelajaran dengan jelas dan tidak menggunakan tema; 3) Evaluasi pembelajaran yang dilaksanakan berpedoman pada RPP yang disusun. Evaluasi dilakukan untuk memperbaiki kegiatan pembelajaran guru, bentuk evaluasi lisan dan tulisan; dan 4) Faktor pendukung adanya kegiatan supervisi yang dilakukan oleh kepala sekolah untuk memperbaiki dan membina kemampuan guru dalam penerapan manajemen pembelajaran. Hambatannya, antara lain dalam membuat perencanaan untuk pembinaan guru-guru, disebabkan karena waktu, sarana dan personil yang tersedia. Kurangnya pelatihan bagi guru-guru, tidak aktifnya sebagian guru dalam kegiatan gugus, seminar, dan kegiatan peningkatan profesi keguruan.Kata kunci: Manajemen, Pembelajaran Guru, dan SD Negeri 1 Peukan Pidie